OPTIMIZATION OF CAFE AND SALON DEVELOPMENT PROJECT MANAGEMENT WITH PERT AND CPM METHODS AT PT DTD - Ryan Swastiputro Adinugroho; Madelan, Sugiyono (Dinasti Publisher, 2021)
The construction of cafe and salon by PT DTD has been delayed in terms of time. The purpose of this study is to calculate the best time optimization and determine the critical path of the cafe and salon construction project at PT DTD. This research is an evaluation of a project that has been completed. The methods used are Critical Path Method (CPM) and Project Evaluation Review Technique (PERT). The software used is POM-QM for Windows. The project runs for 15 months or 62 weeks from the initial target of the contractor being 8 months. Using POM-QM, from the PERT method, the optimum time for the project is 50 weeks. Project optimization can be carried out using PERT and CPM methods with POM QM software.